The study of Difficulties Encountered in Supervision of Construction Projects in the Monitoring System of Iran Using the FMEA and Providing a Solution to Improve it - Ehsan Zeighami; Maedeh Javaheri Barforooshi; Mohammad Javad Taheri Amiri (مهندسی و مدیریت ساخت)
Monitoring and evaluation are of utmost importance, so that without the creation of a coherent and well-established system, will not have a remarkable efficiency. These oversights are targeted to improve and promote the projects / plan execution quality in the organization while utilize the knowledge and experience of specialists in enhancing the researchers’ activity. Today, the construction sector is encountered many disruptions including low quality constructed buildings. In order to cover the technical inspection services of the building, there is a specific oversight on construction, based on rules and regulations on building subjects. However, due to the number of decision-making centers on building standards such as Construction Engineering Organization, Institute of Standards and Industrial Research, Municipality, and the Ministry of Roads and Urban Development, the supervision and technical inspection of the building sector are in difficulty. In this research, firstly, FMEA method will be used to identify and prioritize the factors affecting the monitoring difficulties in the construction projects of Iran. Then, in order to prevent these problems from occurring in the country's construction projects, some course of actions are presented.